1993
DOI: 10.1093/infdis/168.4.897
|View full text |Cite
|
Sign up to set email alerts
|

A Porcine Model of Staphylococcus epidermidis Catheter-Associated Infection

Abstract: The suitability of using catheterized, partially nephrectomized (uremic) pigs to study catheter-associated infection in peritoneal dialysis was investigated. In some pigs, an inoculum of 10(9) cfu of Staphylococcus epidermidis ATCC 35984 was deposited around the catheter exit site and the organism was allowed to colonize over 21 days. The strain was recoverable from tissues and catheter samples at various locations along the catheter tract from inoculated pigs at postmortem examination. Uninoculated control ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Similar experiments were done in partially nephrectomized pigs to observe the changes in uremia (58). After inoculation of the exit site with S. epidermidis , biofilm colonization progressed just as in the rabbit model, with uremia making no apparent difference in its progression from the exit site to the peritoneum (58).…”
Section: Biofilm and Pathogenesis Of Peritonitis: Rabbit Model Of Pdmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar experiments were done in partially nephrectomized pigs to observe the changes in uremia (58). After inoculation of the exit site with S. epidermidis , biofilm colonization progressed just as in the rabbit model, with uremia making no apparent difference in its progression from the exit site to the peritoneum (58).…”
Section: Biofilm and Pathogenesis Of Peritonitis: Rabbit Model Of Pdmentioning
confidence: 87%
“…Similar experiments were done in partially nephrectomized pigs to observe the changes in uremia (58). After inoculation of the exit site with S. epidermidis, biofilm colonization progressed just as in the rabbit model, with uremia making no apparent difference in its progression from the exit site to the peritoneum (58). These studies confirm the validity of the experimental models of biofilm development and its consequences for biofilmrelated peritonitis in PD patients, either from touch contamination during PD exchanges or from the exit site to the peritoneal cavity.…”
Section: Biofilm and Pathogenesis Of Peritonitis: Rabbit Model Of Pdmentioning
confidence: 90%
“…This clearly indicates that the impact of sarA on biofilm formation, at least as defined under in vitro growth conditions, involves a pathway that is independent of the icaADBC operon. The role of ica in vivo has been addressed in S. epidermidis with contradictory results (10,23,41,47,49,55,56,57,62). However, few studies have addressed this issue in S. aureus.…”
Section: Vol 186 2004 Global Gene Expression In S Aureus Biofilms mentioning
confidence: 99%
“…Overall, these studies (Table 1) demonstrate the presence of a microbial biofilm on the catheter surface, despite the absence of infection, suggesting that it is not the infectious process that gives rise to colonization, but rather that biofilms may act as a reservoir of microorganisms. Indeed, it has been hypothesized that the development of peritonitis depends on the initiation of dialysis (Read et al 1989;McDermid et al 1993) and on the ability of microorganisms to disperse from the biofilm (Verger et al 1987;Dasgupta et al 1992). However, further studies are required to elucidate the biofilm-associated infections in PD, as it was found that the microorganisms colonizing the catheter may not parallel those causing the peritonitis (Marrie et al 1983;Rodriguez-Carmona et al 2000).…”
Section: S Epidermidismentioning
confidence: 99%